Accuracy of skin dose mapping in interventional cardiology: Comparison of 10 software products following a common protocol. (February 2021) - Dabin, Jérémie; Blidéanu, Valentin; Ciraj Bjelac, Olivera; Deleu, Marine; De Monte, Francesca; Feghali, Joëlle Ann; Gallagher, Aoife; Knežević, Željka; Maccia, Carlo; Malchair, Françoise; Sans Merce, Marta; Simantirakis, George
Highlights: Four interventional X-ray systems were tested with up to 8 skin dose mapping products. SDM software can make considerable error in specific conditions. No SDM product provided estimates within 40% for all set-ups and systems. Few SDM products provided estimates within 40% for all set-ups on a specific system. Establishing a common QC protocol for testing SDM products is currently unachievable. Abstract: Purpose: Online and offline software products can estimate the maximum skin dose (MSD) delivered to the patient during interventional cardiology procedures. The capabilities and accuracy of several skin dose mapping (SDM) software products were assessed on X-ray systems from the main manufacturers following a common protocol. Methods: Skin dose was measured on four X-ray systems following a protocol composed of nine fundamental irradiation set-ups and three set-ups simulating short, clinical procedures. Dosimeters/multimeters with semiconductor-based detectors, radiochromic films and thermoluminescent dosimeters were used. Results were compared with up to eight of 10 SDM products, depending on their compatibility. Results: The MSD estimates generally agreed with the measurements within ± 40% for fundamental irradiation set-ups and simulated procedures. Only three SDM products provided estimates within ± 40% for all tested configurations on at least one compatible X-ray system. No SDM product provided estimates within ± 40% for all combinations of configurations and compatible systems. The accuracy of the MSD estimate for lateral irradiations was variable and could be poor (up to 66% underestimation). Most SDM products produced maps which qualitatively represented the dimensions, the shape and the relative position of the MSD region. Some products, however, missed the MSD region when situated at the intersection of multiple fields, which is of radiation protection concern. Conclusions: It is very challenging to establish a common protocol for quality control (QC) and acceptance testing because not all information necessary for accurate MSD calculation is available or standardised in the radiation dose structured reports (RDSRs).